Acid-base disarrangement and gastric intramucosal acidosis predict outcome from major trauma - Calvete,José O. (2008)
INTRODUCTION: This prospective non-interventional study intended to assess the prognostic value of gastric intramucosal acidosis in patients with severe trauma admitted to a medical/surgical ICU. METHODS: Gastric tonometer catheters were introduced to measure air PCO2 level (Tonocap device) in forty consecutive critically ill trauma patients. Gastric intramucosal pH, air PCO2 gradient, lactate and acid-base parameters were measured at admission and at 6, 12 and 24 h thereafter. RESULTS: The median age, mean APACHE II and SOFA scores were higher in nonsurvivors than in survivors (p<0.05). There were significant differences in the PCO2 gradient between survivors and nonsurvivors at 12 and 24 hours (10±7 vs. 24±19 mmHg, 13±16 vs. 29±25 mmHg; p<0.05). Gastric intramucosal pH values were lower in nonsurvivors than in survivors, on admission and after 12 or 24 hours (p<0.05). Arterial pH and bicarbonate were lower, lactate concentration higher, and base excess more negative in nonsurvivors. Prediction of outcome (mortality and MODS) at 24 hours of ICU assessed by their ROC curves was similar (p=NS). At 24 hours, air PCO2 gradient > 18 mmHg carried a relative risk of 4.6 for death, slightly higher than a HCO3 <20 mEq/L (RR=4.29) or base excess of <-2 mmol/L (RR=3.65). CONCLUSION: Bicarbonate, base deficit, lactate, gastric intramucosal pH and PCO2 gradient discriminate survivors from nonsurvivors of major trauma. A critical air PCO2 gradient carried the greatest relative risk for death at 24 hours of ICU. Inadequate regional blood flow as detected by a critical PCO2 gradient seems to contribute to morbidity and mortality of severe trauma patients.